Celiac plexus block as a diagnostic tool in suspected pediatric median arcuate ligament syndrome - Selvaraj BJ; Joshi M; Weber G; Yarmush J (Local and Regional Anesthesia, 2019)
Bright Jebaraj Selvaraj,1 Minal Joshi,1 Garret Weber,2 Joel Yarmush1 1Department of Anesthesiology, New York Presbyterian Brooklyn Methodist Hospital, Brooklyn, NY, USA; 2Department of Anesthesiology, Westchester Medical Center, Valhalla, NY, USA Abstract: We report the use of celiac plexus block (CPB) as a diagnostic aid in the evaluation of median arcuate ligament syndrome (MALS) in a pediatric patient. MALS is a rare cause of severe, debilitating, abdominal postprandial pain associated with nausea, vomiting, occasional diarrhea, unintentional weight loss, and abdominal bruit. MALS is a diagnosis of exclusion, after multiple investigations. This is the first case report where CPB was used to confirm candidacy for corrective surgery in the pediatric population and has served as the cornerstone in diagnosis of MALS. Keywords: median arcuate ligament syndrome, celiac plexus block, pediatric, diagnostic